2020
DOI: 10.4209/aaqr.2020.04.0171
|View full text |Cite
|
Sign up to set email alerts
|

Social and Travel Lockdown Impact Considering Coronavirus Disease (COVID-19) on Air Quality in Megacities of India: Present Benefits, Future Challenges and Way Forward

Abstract: The coronavirus disease (COVID-19) created enormous pressure across the globe due to an increasing number of COVID-19 infected cases. All the governments' primary focus is to save humanity from this pandemic problem, and they have lockdown almost the entire nation to stop the spread of infection. This lockdown resulted in a considerable impact on the global as well as a local economy that will take a long time to perform with business as usual scenario. However, improvement in the air quality of the cities acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
235
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(261 citation statements)
references
References 29 publications
21
235
4
1
Order By: Relevance
“…The most signi cant reduction was noticed for PM 2.5, PM10, NO2, NO and CO. Similar observation was also reported from other megacities in India (Sharma et al, 2020;Mahato et al, 2020;Jain and Sharma, 2020) and elsewhere (Xu et al, 2020;Krecl et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…The most signi cant reduction was noticed for PM 2.5, PM10, NO2, NO and CO. Similar observation was also reported from other megacities in India (Sharma et al, 2020;Mahato et al, 2020;Jain and Sharma, 2020) and elsewhere (Xu et al, 2020;Krecl et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…This duration is decided because it comprised the period of the first three phases of lockdown in India. During the lockdown, sources of harmful gases and particulate matters were reduced dramatically, because most of the industries and major movement of vehicles were halted due to which air quality is improved up to a remarkable extent throughout the world (Broomandi et al 2020 ; Gautam and Hens 2020a ; Gautam and Trivedi 2020 ; Jain and Sharma 2020 ; Li et al 2020 ; Zhang et al 2020 ). During the current study period, a major movement of people is restricted due to lockdown, and henceforth other transmission factors of COVID-19 are targeted to nullify, reduce, or control up to a certain level.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, in India, the first lockdown was announced on March 25, 2020 with more consecutive lockdowns ahead. Lockdown possessed a serious effect on the economy of countries but air quality and environment improved (Gautam 2020 ; Jain and Sharma 2020 ; Metya et al 2020 ; Nakada and Urban 2020 ), because most industries and transportation halted during the period of lockdown. In this work, the study period considered for the investigation is the lockdown period, so that the relationship of meteorological parameters with COVID-19 cases is studied in a controlled manner that may help in better anticipation of the relationship between the virus and weather parameters.…”
Section: Introductionmentioning
confidence: 99%
“…reported an improvement in air quality index in Delhi and nearby region during initial days of COVID-19 induced lockdown (during 25-30 March, 2020). Jain and Sharma (2020) (Jain and Sharma, 2020) reported a decrease in NO2 concentration by ~51% during 25 th March -6 th April 2020 compared to 10 th -20 th March 2020 over Delhi. Mahato et al (2020) reported ~53% and ~18% reduction in NO2 and SO2 concentration respectively during 25 th March -14 th April, 2020…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Over other regions around the world, studies (Devi et al, 2020;Fan et al, 2020;Siciliano et al, 2020;Xu et al, 2020) have noted a reduction in pollution and improvement of air quality during the lockdown period. Recent studies focusing on the early stages of the lockdown studies have reported a decrease in atmospheric pollutants over different regions in the Indian subcontinent (Devara et al, 2020;Jain and Sharma, 2020;Mahato et al, 2020;Sharma et al, 2020). Devara et al (2020)…”
Section: Introductionmentioning
confidence: 99%